Rolandic beta-band activity correlates with decision time to move. (11th March 2016) - Jo, Han-Gue; Hinterberger, Thilo; Wittmann, Marc; Schmidt, Stefan
Highlights: Neural oscillations were examined during voluntary movements. Beta ERD is relevant for subjective reports on decision timing to move. The higher the increase of beta ERD the earlier the decision time to move. Abstract: Research findings link rolandic beta-band activity to voluntary movements, but a linkage with the decision time to move remains unknown. We found that beta-band (16–28 Hz) activity shortly before the movement onset is relevant for the decision time to move: the more pronounced the decrease in beta-band synchronization, the earlier the subjective experience of the decision to move. The linkage was relevant regarding 'decision', but not regarding 'intention' timing that has been often applied in the study of free will. Our findings suggest that oscillatory neural activity in the beta-band is an important neural signature pertaining to the subjective experience of making a decision to move.